Psychological resources for well-being in high-risk policing: The roles of gratitude and optimism among members of the Gegana Detachment - Aulia Aulia; Yuli Yulianti; Riski Nur Amalia (Universitas Ahmad Dahlan, 2026)
High job demands and occupational risks may adversely affect the subjective well-being of members of the Gegana Detachment, an elite tactical unit of the Indonesian National Police. This study aimed to examine the roles of gratitude and optimism in predicting subjective well-being among Gegana personnel. A quantitative cross-sectional study was conducted involving 120 active members of the Gegana Detachment who had at least one year of service and were recruited using purposive sampling. Data were collected using the Subjective Well-Being Scale, the Gratitude Questionnaire-6 (GQ-6), and an optimism scale developed based on Seligman's theoretical framework. Multiple linear regression analysis revealed that gratitude and optimism jointly served as significant positive predictors of subjective well-being (R=.794, F=99.823, p<.001). Both variables also made significant individual contributions, with optimism emerging as the stronger predictor. These findings suggest that strengthening gratitude and optimism may represent an effective psychological strategy for enhancing subjective well-being among law enforcement personnel working in high-risk occupational environments.